Universal Salt Iodinization is not that Universal - A study among school age children in Mandla District, Madhya Pradesh. - Bali, Surya; Gupta, Arti (Indian Journal of Community Health, 2019)
Background: Iodine deficiency is a preventable cause of brain damage. Aims &Objectives: The present study was conducted to determine the prevalence of goiter in school going children clinically, to assess the iodine status (urinary iodine excretion) of school children, and to assess the iodine content of the salt consumed by the population. Materials and Methods: It is school based cross-sectional study, conducted in Mandla district of Madhya Pradesh state in central India in 2016. The study participants were school children in 6-12 years of age. Probability-proportional-to-size cluster sampling was used. Palpation method was used to identify the presence of goiter. Urine samples were collected and median urinary iodine excretion was found. The salt samples were also collected from the households and local market to determine the iodinization status. Results: A total of 2700 school children were studied. The total goitre rate was 0.74%. Among those clinically palpable goiter 15(75%) were girls. The prevalence of goitre higher among girls was statically significant with p=0.025. All the cases of clinically palpable goiter belonged to caste other than general with p<0.001. The median urinary iodine excretion of 270 urine samples of school children was 184 µg/l. The prevalence of iodine deficiency disorders using urinary iodine excretion as indicator in the present study was 22.9% Seven percent of the samples had median urinary iodine The normal iodine content i.e more than the 15 ppm iodine was present in 84% of samples collected from households. Conclusion: The children of Mandla district of Madhya Pradesh had low prevalence of goiter. However, there is significant burden of goiter among backward classes.